Corpus callosal lipoma extending as nasal encephalocoel/cranial lipomeningocoel. (November 2017) - Shah, Abhidha; Rai, Survendra; Goel, Atul
Highlights: A case is reported wherein the intracranial lipoma communicated with the exterior into the paranasal air sinus. The presentation of the patient simulated that observed in a case with nasal encephalocoel. Such communication of paranasal sinus and intracranial compartment lipoma presents an opportunity to evaluate the embryogenesis of the brain. Abstract: A hitherto unreported case is presented wherein a 2 year old child had a 'cranial lipomeningocoel' or a 'nasal lipo-encephalocoel'. The child presented with a growing mass in the base of the nose. Investigations revealed that the nasal mass was a lipoma that was an extension of intracranial lipoma. The intracranial component extended up to corpus callosum. Resection of the extracranial extension and basal reconstruction resulted in cosmetic recovery.